Silica: A lung carcinogen. (10th December 2013) - Steenland, Kyle; Ward, Elizabeth
Abstract Silica has been known to cause silicosis for centuries, and evidence that silica causes lung cancer has accumulated over the last several decades. This article highlights 3 important developments in understanding the health effects of silica and preventing illness and death from silica exposure at work. First, recent epidemiologic studies have provided new information about silica and lung cancer. This includes detailed exposure‐response data, thereby enabling the quantitative risk assessment needed for regulation. New studies have also shown that excess lung mortality occurs in silica‐exposed workers who do not have silicosis and who do not smoke. Second, the US Occupational Safety and Health Administration has recently proposed a new rule lowering the permissible occupational limit for silica. There are approximately 2 million US workers currently exposed to silica. Risk assessments estimate that lowering occupational exposure limits from the current to the proposed standard will reduce silicosis and lung cancer mortality to approximately one‐half of the rates predicted under the current standard. Third, low‐dose computed tomography scanning has now been proven to be an effective screening method for lung cancer. For clinicians, asking about occupational history to determine if silica exposure has occurred is recommended. If such exposure has occurred, extra attention might be given to the early detection of silicosis and lung cancer, as well as extra emphasis on quitting smoking. CA Cancer J Clin 2014;64:63–69.©2013 American Cancer Society, Inc.